Religion, rule of law, or the family honour? moral commitment among Lebanese children - Ghosn, Irma-Kaarina (2009)
The present study examined the moral development of Lebanese 1st graders. Interviews with sixty-three Lebanese children (28 girls and 35 boys, ages 6–7.5) were analysed for the study. The children (25 Christian and 38 Muslim) were interviewed about moral dilemmas children of this age might encounter in their daily life. The data revealed that children’s reasoning differed based on the content of the dilemma, with both Kohlberg’s justice-focused morality and Gilligan’s care-focused morality evident. Both boys and girls considered emotions and relationships equally. When children’s responses were categorized into Kohlberg’s four moral orientations (normative, utilitarian, harmony-serving, justice), the majority of responses reflected normative orientation, while the three other orientations were also represented. Second level analysis showed that Lebanese children’s moral decisions were also guided by the cultural constructs ofwajibāt (social duties/obligations) andsharaf (honour), with religion and concern for the rule of law also appearing in their of responses.